MENAKAR KUALITAS PENDIDIKAN BERKARAKTER DI INDONESIA - Maslathif Dwi Purnomo (Universitas Islam Negeri Sumatera Utara Medan, 2016)
Education which character seemed to be a new breath for education quality improvement efforts in this country. The noble effort amid declining public confidence in the education system that is applied in this country. But behind it all, the declaration of interest in character education has many obstacles and challenges. The challenge comes from both within the scope of education itself and external factors that are clearly threatening to the success of character education who wants to go. So it is like to be a bitter pill for the managers of education. Can character education really happen in our country with the reality of a nation that is happening now? The answer is in the minds of each of us